Overweight and Weight Loss Maintenance - Anne Mathews; Lauren Foster; Wendy Dahl (EDIS)
For many people, weight loss is a chronic battle. Popular diets are often unsuccessful because they cannot be followed permanently. There is no magic diet to make you instantly shed pounds, but some good tips for steady, long-term weight loss are listed in this 2-page fact sheet written by Anne Mathews, Lauren Foster, and Wendy Dahl, and published by the UF Department of Food Science and Human Nutrition, February 2013.